THE INVERSE RELATIONSHIP BETWEEN THE ESSENCE OF INFLATION AND UNEMPLOYMENT AND ANTI-INFLATIONARY POLICIES - Z. M. Qudratova (Bright Mind Publishing, 2025)
This article examines the essence of the term inflation, types of its calculation, theoretical aspects of the inverse relationship between inflation and unemployment and its impact on the economy, and analyzes anti-inflationary policy.